Optimasi Performa Mesin Gyratory Crusher I dengan Menggunakan Metode OEE & Six Big Losses di PT XYZ - Seftia Ady Candra; Fuad Achmadi (Institut Teknologi Adhi Tama Surabaya, 2022)
Indonesia is an archipelagic country that has various types of natural resources, both renewable and non-renewable. Of the many natural resources, there are some that have been carried out in the mining process. In processing mining products, a processing method is needed to be able to use them for industrial and construction purposes. There are processing methods in the form of traditional tools and some use modern tools. These tools must be properly maintained in order to operate optimally and produce high quality products in accordance with the production plan. In this research, optimization of Gyratory Crusher 1 engine performance using OEE Six Big Losses method at PT XYZ. PT XYZ is a company engaged in construction support specializing in the supply of milled C material in the form of andesite stone which was established in 1982. The data used for the calculations were obtained from daily reports on the Gyratory Crusher machine 1 Period 1 - 30 November 2020. From the problem formulation and the research results obtained: 1) Determining the Availability Performance value of Gyratory Crusher I can be seen from the average value of availability rate of 87.27%, performance efficiency of 80.27% and Quality Ratio value of 94.46%. The results are in accordance with the standards, this can be seen from the availability and quality values which are above world standards. However, the performance rate variable is still less than the standard due to speed losses, namely the actual engine speed is not in accordance with the ideal speed, 2) Increasing the Availability number by optimizing the Gyratory Crusher I Performance, which can be increased by eliminating the six big losses, especially reduced speed losses. which is very dominant from the calculation results in this study, which is 23.08% and idling and minor stoppages losses in second place with a value of 8.79% then equipment failures losses in third place with a value of 7.94%. Furthermore, the effectiveness of the machines can be increased by finding the root cause of the low OEE using the fishbone diagram method, then performing preventive and predictive maintenance, especially on critical and very critical machines/equipment.